Toward Assessing the Quality of Subtitles based on SRT Files Processing - Borges, Thiago Felipe Corrêa; Guimarães, Rodrigo Laiola (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
In order for subtitles to fulfill their objective of enriching users' experience, it is necessary that, during the subtitling process (creation of subtitles), "good practices", usually specified in subtitling guides, are taken into account. In this context, this work uses an approach based on the processing of SRT files to assess the degree of compliance of subtitles in relation to the recommendations of a reference guide considered in the subtitling process. Our preliminary results show how meticulous is the process performed by those who aim at providing a satisfactory quality of experience (QoE) for viewers of the audiovisual content.